A COMBINATION REVIEW ON EFFECT OF CITRUS JUICE AND METRONIDAZOLE IN INFLAMMATORY BOWEL DISEASE - Deeksha; Saini, Shalini; Bhatt, Meenakshi (International Journal of Research -GRANTHAALAYAH, 2023)
The set of inflammatory disorder known’s as inflammatory bowel disease (IBD) affects the gastrointestinal tract and is chronic and complicated condition. Both Crohn's disease and ulcerative colitis, the two main types of inflammatory bowel disease, cause inflammation in the digestive system. Chron's disease can affect any part of the gastrointestinal tract, while ulcerative colitis only affects the colon and rectum. They induce the inflammatory symptoms of swelling, discomfort, an increase in body temperature, redness, and itching. The diagnosis of inflammatory bowel disease requires a careful examination of the patient's medical history, a physical examination, and other tests. Blood tests, imaging scans, and occasionally biopsies. The goal of treatment is to reduce inflammation and symptoms, usually with a combination medication, dietary modification, and occasionally surgical intervention. IBD cannot be cured, however improvements in medical therapy have greatly enhanced patient outcome and care. To effectively manage IBD and improve the quality of life for patients suffering from this difficult condition, regular medical checkup and adherence to treatment plans are essential. The best IBD management and patients well- being depends critically on early detection, prompt intervention and continued support from healthcare provides. Metronidazole and mesalamine drugs are used as different dose in the treatment of IBD inflammation. Some condition citrus juice also used as a treatment because they help in the immune power.